Age-Related Physiologic Thinning Rate of the Retinal Nerve Fiber Layer in Different Levels of Myopia - Daun Jeong; Kyung Rim Sung; Youn Hye Jo; Sung-cheol Yun (Journal of Ophthalmology)
Purpose. To investigate the effect of refractive error on the physiologic thinning rate of the retinal nerve fiber layer (RNFL) in healthy eyes. Materials and Methods. This study analyzed 223 eyes of 141 healthy subjects followed for more than 5 years and underwent at least five serial spectral domain optical coherence tomography (SD-OCT) examinations. Longitudinal RNFL measurements were analyzed by linear mixed models incorporating follow-up duration, baseline RNFL thickness, spherical equivalent (SE), age, intraocular pressure, and visual field mean deviation. Thinning rates were classified according to SE into three groups: nonmyopic (NM; >0 D), mild-to-moderately myopic (MM; >–6 D and ≤0 D), and highly myopic (HM; ≤–6 D). Results. The overall slopes of change in RNFL thickness over time in the NM, MM, and HM groups were −0.305 ± 0.128, −0.294 ± 0.068, and −0.208 ± 0.097 μm/yr, respectively. Slopes of RNFL thickness changes in these groups were −0.514 ± 0.248, −0.520 ± 0.133, and −0.528 ± 0.188 μm/yr, in the superior quadrant; −0.084 ± 0.145, 0.107 ± 0.082, and −0.161 ± 0.112 μm/yr, in the temporal quadrant; −0.807 ± 0.242, −0.794 ± 0.130, and −0.727 ± 0.183 μm/yr, in the inferior quadrant; and 0.160 ± 0.157, 0.118 ± 0.084, and 0.429 ± 0.119 μm/yr, in the nasal quadrant. Overall and in all four quadrants, there was no significant difference in the rate of RNFL thickness change among the three groups. Conclusions. Refractive error did not affect the physiologic thinning rate of RNFL when assessed by SD OCT.